Frasnian (Upper Devonian) lithostratigraphy of the Bernesga Valley (Cantabrian Mountains, NW Spain) - van Loevezijn, Gerard (Geologos, 2025)
Sequence stratigraphic units are defined in terms of changes in relative sea level, and not on the compositional similarity of the lithology of the rock units. Sequence boundaries were used to support the formal definitions of the Gordón Member and the Millar Member of the Frasnian Nocedo Formation (Cantabrian Mountains). Therefore, each member consists of a broad range of lithologies. In this study each sequence of the Nocedo Formation is subdivided into formal lithological units and from each unit the stratigraphic characteristics and spatial distribution pattern is presented. Within one sequence the lithological units have gradational contacts, and their lateral distribution is consistent and complementary, allowing the understanding of the palaeogeographic picture of the region.